Predictors and Clinical Utility for Positive Abdominal Imaging Findings in Patients Presenting with Peritoneal Dialysis Associated Peritonitis: A Large Regional Health Service Perspective - Dr Alexander M Renehan; Mr Michael J Garrett; Dr Chau Wang Ng (Australasian Journal of Clinical Nephrology, 2026)
Introduction: Peritoneal dialysis (PD) associated peritonitis is a common yet serious complication for those undergoing PD. The role of imaging patients presenting with suspected PD peritonitis is unknown. In addition to healthcare costs and patient exposure to ionising radiation, residual kidney function may be at risk with repeated contrast administration. The aim of this study is to understand the indications and ultimate clinical utility of abdominal imaging in patients presenting with PD peritonitis to a large regional health service Methods: Retrospective analysis of patients presenting with PD peritonitis to Bendigo Health was conducted. Use and modality of abdominal imaging was recorded. Findings were categorised as positive when congruent with the patient’s presenting abdominal pain, or incidental when unrelated. Where imaging was performed, overall influence on patient care was assessed. Results: There were 53 episodes occurring across 31 patients admitted with PD peritonitis between December 2016 to February 2024. Abdominal imaging was performed in 81.13% of these episodes (n=43). Positive imaging findings occurred in 31.31% (n=16), with constipation being frequently identified. Incidental findings occurred in 27.45% (n=14), while 41.18% (n=21) showed no abnormalities. No patient or episodic factors were significantly associated with positive imaging findings. Of patients imaged, clinical management was influenced in 20.93% (n=9) of cases. Conclusion: Abdominal imaging in suspected PD peritonitis demonstrates low clinical utility, with positive findings directly influencing management in only a minority of cases. There is insufficient evidence to routinely recommend imaging for this cohort.